2016
DOI: 10.1007/s10815-016-0766-5
|View full text |Cite
|
Sign up to set email alerts
|

Reanalysis of human blastocysts with different molecular genetic screening platforms reveals significant discordance in ploidy status

Abstract: The results of these studies reinforce the prevalence of inconsistencies during PGS evaluation of trophectoderm biopsies possibly due to variations in platform sensitivity and heightening concerns over the clinical tractability of such technology in human ARTs..

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 31 publications
0
18
0
Order By: Relevance
“…One study found a 30.1% mosaicism rate in TE biopsies from 1547 blastocysts similar to the 28% rate identified in over 2000 biopsies in another study . Analyses of multiple biopsies from the same embryo identified mosaicism rates of 50% (5/10), 37.5% (3/8), 44% (16/36), 34.5% (20/58) and 14% (4/29) . Collectively, therefore, based on multiple‐biopsy analyses, blastocyst mosaicism rates range from 14% to 50% with a mean of 36%, much higher than previously thought.…”
Section: Can Pgt‐a Definitively Assign Abnormality?mentioning
confidence: 77%
“…One study found a 30.1% mosaicism rate in TE biopsies from 1547 blastocysts similar to the 28% rate identified in over 2000 biopsies in another study . Analyses of multiple biopsies from the same embryo identified mosaicism rates of 50% (5/10), 37.5% (3/8), 44% (16/36), 34.5% (20/58) and 14% (4/29) . Collectively, therefore, based on multiple‐biopsy analyses, blastocyst mosaicism rates range from 14% to 50% with a mean of 36%, much higher than previously thought.…”
Section: Can Pgt‐a Definitively Assign Abnormality?mentioning
confidence: 77%
“…In this issue of JARG, Tortoriello et al report highly divergent outcomes when trophectoderm biopsies from the same embryos were referred for PGS 2.0, at different laboratories, using varying assay platforms [11]. Chromosomal analyses after two sequential trophectoderm biopsies from the same embryos revealed only 11 % (3/27) ploidy detection concordance between microarray-based comparative genomic hybridization (aCGH) and next-generation sequencing (NGS).…”
Section: Pgs and Mosaicismmentioning
confidence: 99%
“…In addition to the here discussed manuscript [11], using NGS, a recently published study [14], evaluated in eight topquality embryos the concordance of multiple trophectoderm biopsies. In four embryos, the inner cell mass was also analyzed separately.…”
Section: The Biology Of Mosaicismmentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, Tortoriello et al performed a second trophectoderm biopsy in embryos initially deemed by cytogenetics to be aneuploid and found that 9/27 (33 %) were euploid when using a different technology and a different genetic laboratory [18]. Gleicher et al found a similar false positive rate (36.4 %) when re-testing dissected embryos initially reported as aneuploid [19].…”
mentioning
confidence: 99%